Comparison of COVID-19 second wave with the first wave of a tertiary care center in Western Uttar Pradesh, India - Mehra, Ridhi; Gupta, Udita (International Journal Of Community Medicine And Public Health, 2024)
Background: During this COVID-19 pandemic, there were two distinct waves observed in almost every country. A second wave beginning in March 2021 was much more devastating than the first, with shortages of vaccines, hospital beds, oxygen cylinders and other medical supplies in parts of the country. Methods: This retrospective observational study was conducted at Saraswathi Institute of Medical Sciences (SIMS), Hapur, Uttar Pradesh, India from March 2020 to May 2021. All COVID positive patients were included from the hospital records. The data was analysed by appropriate statistical techniques and tests. Results: There were two distinct waves of COVID-19: wave 1 from 01 March 2020 to 31 December 2020 and wave 2 from 01 January 2021 to 31 May 2021. On admission, the mean (±SD) age of patients in the pandemic period was 45.97 years (±18.41). Males acquired COVID-19 infection in higher number in all age group compared to females in both waves. There was a higher male to female patient percentage who died in hospital from COVID-19 in wave 1 and wave 2 (χ2=0.027, p=0.869). Conclusions: A comparative analysis of the first wave with that of the second wave can suggest a better way for the policymakers and stakeholders in the management of COVID-19 recurrence or its severity in India and other countries.